Treatment patterns in moderate-to-severe plaque psoriasis: results from a Belgian cross-sectional study (DISCOVER). (4th July 2017) - Lambert, Julien; Ghislain, Pierre-Dominique; Lambert, Jo; Cauwe, Bénédicte; Van den Enden, Maria
Abstract: Purpose: The present study aimed to evaluate current treatment patterns and achievement of treatment goals in Belgian patients with moderate-to-severe plaque psoriasis. Materials and methods: This cross-sectional observational study (DISCOVER) was conducted in 2011 − 2012 in Belgian dermatology centers. Patient data were collected during a single visit and included information on psoriasis management and severity (PASI and DLQI). Treatment success was defined according to the current European consensus treatment goal algorithm. Results: Of the 556 patients included in the study, 38.1% reported no current treatment or only topicals, 34.2% were being treated with traditional systemics and/or phototherapy, and 29.5% with biologics. Methotrexate (11.7%) was the most commonly prescribed traditional systemic and adalimumab (14.2%) was the most commonly prescribed biologic agent at the time of the study. The percentage of patients achieving treatment goals was significantly higher in biologic-treated patients (73.1%) compared to those using traditional systemics (50.6%), phototherapy (41.1%), or no treatment/only topicals (20.9%; p < .001). Conclusions: Nearly 40% of Belgian patients with moderate-to-severe psoriasis in the DISCOVER study were undertreated despite the severity of their disease. Undertreatment of psoriasis remains a problem in Belgium and more effective educational strategies are needed to ensure the best treatment outcome for these patients.